Gender‐specific genetic influence of rs1111875 on diabetes risk: Insights from the Taiwan biobank study - Chih‐Wei Chiang; Ying‐Hsiang Chou; Chien‐Ning Huang; Wen‐Yu Lu; Yung‐Po Liaw (Journal of Diabetes Investigation)
ABSTRACT Background This study investigates the gender‐specific genetic influence of the single nucleotide polymorphism (SNP) rs1111875 on diabetes risk within the Taiwanese population using data from the Taiwan Biobank. Diabetes mellitus, particularly type 2 diabetes (T2D), is influenced by genetic factors, and the rs1111875 SNP near the hematopoietically expressed homeobox (HHEX) gene has been linked to T2D susceptibility. Methods The study included 69,272 participants after excluding those from arsenic‐polluted areas and those with incomplete data. Logistic regression models were used for analyses. Results The analyses revealed that the CT genotype of rs1111875 was associated with an increased risk of diabetes (OR = 1.092, 95% CI = 1.030–1.157, P = 0.003), as was the TT genotype (OR = 1.280, 95% CI = 1.165–1.407, P < 0.001). The effect was more pronounced in women (CT: OR = 1.118, 95% CI = 1.036–1.207, P = 0.004; TT: OR = 1.404, 95% CI = 1.243–1.585, P < 0.001). Men exhibited a higher overall risk of diabetes (OR = 1.565, 95% CI = 1.445–1.694, P < 0.001) and had a higher prevalence (12.71% vs 7.80%, P < 0.001) compared to women. Conclusions The findings underscore the importance of considering gender differences in genetic studies of diabetes and suggest that personalized diabetes management strategies should account for both genetic and gender‐specific risk factors. This research contributes to the broader understanding of genetic determinants of diabetes and their interaction with gender, aiming to enhance personalized healthcare strategies for diabetes prevention and treatment.